The new couple in 5b eaudiobook A novel. - Unger, Lisa (Harlequin Audio, 2024)
"Spine-tingling fun." —People "Lisa Unger, you've done it again." —Sarah Michelle Gellar, Emmy Award-winning actress A couple inherits an apartment with a spine-tingling past in this unputdownable thriller from the New York Times bestselling author of Secluded Cabin Sleeps Six. Rosie and Chad Lowan are barely making ends meet in New York City when they receive life-changing news: Chad's late uncle has left them his luxury apartment at the historic Windermere in glamorous Murray Hill. With its prewar elegance and impeccably uniformed doorman, the building is the epitome of old New York charm. One would almost never suspect the dark history lurking behind its perfectly maintained facade. At first, the building and its eclectic tenants couldn't feel more welcoming. But as the Lowans settle into their new home, Rosie starts to suspect that there's more to the Windermere than meets the eye. Why is the doorman ever-present? Why are there cameras everywhere? And why have so many gruesome crimes occurred there throughout the years? When one of the neighbors turns up dead, Rosie must get to the truth about the Windermere before she, too, falls under its dangerous spell. Looking for more spine-tingling thrillers? Check out these other titles by New York Times bestselling author Lisa Unger: Under My Skin The Stranger Inside Confessions on the 7:45 Last Girl Ghosted Secluded Cabin Sleeps Six